Proteomics Analysis Reveals Bacterial Antibiotics Resistance Mechanism Mediated by ahslyA Against Enoxacin in Aeromonas hydrophila - Li, Zhen; Zhang, Lishan; Song, Qingli; Wang, Guibin; Yang, Wenxiao; Tang, Huamei; Srinivasan, Ramanathan; Lin, Ling; Lin, Xiangmin (Frontiers in Microbiology, 2021)
Bacterial antibiotic resistance is a serious global problem; the underlying regulatory mechanisms are largely elusive. The earlier reports states that the vital role of transcriptional regulators (TRs) in bacterial antibiotic resistance. Therefore, we have investigated the role of TRs on enoxacin (ENX) resistance in Aeromonas hydrophila in this study. A label-free quantitative proteomics method was utilized to compare the protein profiles of the ahslyA knockout and wild-type A. hydrophila strains under ENX stress. Bioinformatics analysis showed that the deletion of ahslyA triggers the up-regulated expression of some vital antibiotic resistance proteins in A. hydrophila upon ENX stress and thereby reduce the pressure by preventing the activation of SOS repair system. Moreover, ahslyA directly or indirectly induced at least 11 TRs, which indicates a complicated regulatory network under ENX stress. We also deleted six selected genes in A. hydrophila that altered in proteomics data in order to evaluate their roles in ENX stress. Our results showed that genes such as AHA_0655, narQ, AHA_3721, AHA_2114, and AHA_1239 are regulated by ahslyA and may be involved in ENX resistance. Overall, our data demonstrated the important role of ahslyA in ENX resistance and provided novel insights into the effects of transcriptional regulation on antibiotic resistance in bacteria.